The impact of the use of focused listening strategies for the improvement of B2 level english students' listening-comprehension performance - Rodríguez Domínguez, kary Nohemy; Contreras Cárcamo, Mauricio Salvador; Megías, Manuel; Carranza Campos, Miguel Angel (San Salvador, El Salvador : Universidad de El Salvador, 2010)
Action research, typically directed by the teacher, is the process of testing ideas in the classroom, analyzing its results, and deciding the implementation of the new ideas that worked, in a systematic way or beginning the process again with another idea. The results of this type of research are expected to be practical and relevant to the researcher and the coworkers. Critical reflection is the most important aspect of qualitative research and it can provide effective strategies for improving competencies in any educational field. This action research intends to find out if some strategies to improve the students’ listening comprehension performance can be of benefit for the learners to start coping with the difficulties many students find when facing oral texts in the FL classroom. For this research, we will take into account the information proposed by The Common European Framework of Reference for Languages: Learning, Teaching, Assessment (CEFRL) about listening comprehension of oral texts and a number of strategies that, in our opinion, can help to overcome difficulties when dealing with this skill.
Anexos
Thesis in order to obtain the degree of -- (Maestría en didáctica del Idioma Inglés) -- Universidad de El Salvador, San Salvador, 2010
Audiencia general.
La tesis también está en formato digital.
Keywords: Inglés -- Enseñanza; Métodos de enseñanza